THE FUNCTION AND PURPOSE OF AIRCRAFT ACCIDENT INVESTIGATION ACCORDING TO THE INTERNATIONAL AIR LAW - Atip Latipulhayat (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2015)
The main objective of an aircraft accident investigation is to find out the most probable causes of such accident. This represents a technical investigation in nature. At the practical level, however, this report is often used as legal evidence before the court. This paper argues that the main purpose of an aircraft acccident investigation is technical in nature and judicial investigation is carried out when the technical investigation found elements of crime that has been alleged as the most probable cause of the accident. Menurut Konvensi Chicago 1944, tujuan utama suatu investigasi kecelakaan pesawat udara adalah untuk menemukan penyebab terjadinya kecelakaan tersebut. Jadi, investigasi ini bersifat teknis. Namun, laporan investigasi ini seringkali dijadikan alat bukti di pengadilan khususnya apabila faktor kesalahan manusia dianggap sebagai penyebab utama terjadinya kecelakaan tersebut. Investigasi teknis berubah menjadi investigasi yuridis. Tulisan ini berpendapat bahwa hakikat investigasi kecelakaan pesawat udara adalah bersifat teknis dan investigasi yuridis hanya akan dilakukan apabila laporan investigasi teknis menunjukkan adanya elemen kriminal.